Implementasi Media “Carika” Berbasis Model PBL Upaya Peningkatan Hasil Belajar Bahasa Indonesia pada Peserta Didik Kelas IV - Alya Putri Maradika Ningrum; Panca Dewi Purwati (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The problem of learning difficulties of grade IV students of SD Negeri Kandangan 04, Semarang Regency is in the subject Indonesian the procedure text material, causing the learning outcomes of some students to have not reached completion. The purpose of this study is to describe the implementation of the media "CariKa" based on the PBL model of class IV procedure text material and its effect on the understanding of text material, procedures and learning outcomes of students. The subjects in the study were grade IV students of SD Negeri Kandangan 04 Semarang Regency totaling 23 students. Data analysis techniques used include tests, observation and documentation. Data analysis uses qualitative descriptive analysis. The results of the study showed that the application of the PBL model of class IV procedural text material with the help of "CariKa" media in grade IV SD Negeri Kandangan 04 Semarang Regency made it easier for students to understand the procedure text material and there was a change in the improvement of the learning outcomes of the summation material as seen from the comparison of the percentage of completeness of pretest and posttest scores with an increase, namely from 30.44% to 65.22%. Keywords: Learning outcomes; Learning Indonesian;Problem Based Learning; Wordwall